Rasio Likuiditas dalam Menaksir Kapasitas Financial pada PT. Indofood Sukses Makmur - Afifah Afifah; Yasmir Yasmir; Nurul Sabani; Devita Natalia; Hariany Idris (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2023)
The purpose of this research is to gain knowledge about the company's financial capabilities related to PT. Indofood Sukses Makmur, Tbk by utilizing a financial ratio measurement tool and referring to the type of liquidity ratio for 2019 to 2020. The results of this study cannot be separated from the research technique itself, observers use historical data from the company's annual financial statements. The shape of this research is descriptive quantitative research, which refers to the direct processing by observers of the annual financial report data obtained from PT. Indofood Sukses Makmur, Tbk for the period 2019 to 2020. The results of the study illustrate that by using a liquidity ratio measuring instrument, PT. Indofood Sukses Makmur, Tbk, with reference to the Current Ratio and Quick ratio, describes the financial condition in a very good and good condition. Meanwhile, for the company's cash ratio, it describes the company's poor condition in paying off its short-term debt by using the company's cash funds.